Correlation of Eight (8) Polymorphisms and Their Genotypes with the Risk Factors of Cardiovascular Disease in a Black Elderly Population - Joseph Musonda Chalwe; Christa Johanna Grobler; Wilna Hendrika Oldewage-Theron (Current Issues in Molecular Biology)
Single nucleotide polymorphisms (SNPs) have been associated with the development of cardiovascular diseases (CVDs). This study correlated eight SNPs with the risk factors of CVD in a black elderly population. Genotyping was used to detect eight polymorphisms; rs675 (ApoA-IV), rs699 (Angiotensinogen (AGT)), rs247616 and rs1968905 (Cholesteryl ester transfer protein (CETP)), rs1801278 (Insulin receptor substrate 1 (IRS-1)), rs1805087 (Methylenetetrahydrofolate reductase (MTHFR)) and rs28362286 and rs67608943 (Proprotein convertase subtilisin/kexin type 9 (PCSK9)), as well as their genotypes in deoxyribonucleic acid (DNA) extracted from peripheral blood. The cardiovascular risk (CVR) measurements were conducted on a Konelab 20i Thermo Scientific autoanalyzer and an enzyme-linked immunoassay (ELISA) assay. International Business Machines Corporation (IBM)® Statistical Package for the Social Sciences ® (SPSS) version 28 was used for statistical analysis. The heterozygous and homozygous genotypes of the eight polymorphisms were detected with the corresponding CVD risk factors. Subgroup analysis indicated that certain genotype carriers exhibited variations in their concentrations of CVR factors compared to others; however, these differences did not reach statistical significance. For example, carriers of the G genotype of the rs699 polymorphism showed marginally different blood pressure readings compared to the AG genotype carriers. The multiple linear regression analysis indicated that the only significant association was between PCSK9 and the rs28362286 (p = 0.029) polymorphism. The findings of our study show that single nucleotide polymorphisms are disseminated across the human genome. The heterozygous and homozygous genotypes of the SNPs require further investigation as they may have independent and possible collective roles in increasing the risk of CVDs.